Microbiology laboratories involved in disease and antimicrobial resistance surveillance: Strengths and challenges of the central African states - Passoret Vounba; Severin Loul; Ludovic F. Tamadea; Joël F.D. Siawaya (AOSIS, 2022)
Laboratory systems have been largely neglected on the margins of health systems in Africa. However, since the 2000s, many African countries have benefited from massive investments to strengthen laboratory capacities through projects fighting priority diseases (HIV/AIDS, tuberculosis, malaria). This review examined the laboratory capacities of the Economic Community of Central African States (ECCAS). Online research using specific terms was carried out. Studies published between 2000 and 2021 on the role of the laboratory in disease and antimicrobial resistance surveillance in the 11 ECCAS countries were considered. The number of human and animal health laboratories meeting international standards was very low in the sub-region. There were only seven International Organization for Standardization (ISO) 15189-accredited human health laboratories, with five in Cameroon and two in Rwanda. There were five high biosafety level (BSL) laboratories (one BSL3 laboratory each in Cameroon, the Central African Republic, Democratic Republic of Congo and the Republic of Congo, and one BSL4 laboratory in Gabon) and three ISO 17025-accredited laboratories in the ECCAS sub-region. Only six countries currently have whole-genome sequencing devices, which is insufficient for a sub-region as large and populous as ECCAS. Yet, a plethora of pathogens, particularly haemorrhagic viruses, are endemic in these countries. The need for laboratory capacity strengthening following a One Health approach is imperative. Since emerging and re-emerging zoonotic infectious diseases are projected to triple in frequency over the next 50 years and given the inextricable link between human and animal health, actors in the two health sectors must collaborate to preserve world health.